Efficient management and storage of a multiversion OWL 2 DL domain ontology. Issue 2 (11th December 2018) - Bayoudhi, Leila; Sassi, Najla; Jaziri, Wassim
Abstract: Ontology is the chief technology to model domain knowledge and fix its heterogeneity. Knowledge evolution is unavoidable in all fields, and ontology should reflect such an evolution while preserving its consistency. The access to an ontology evolution history is also a crucial need. Thereby, ontology versions should be stored efficiently. To address these requirements, some works focused only on managing ontology inconsistency. To this end, they adopted an a posteriori approach that checks inconsistency after its occurrence. Others have mainly focused on some ontology versioning aspects other than the storage and the consistency preservation issues. Specifically, the state of the art storage strategies perform well some typical queries at the cost of a high storage space. Strategies with low space overhead lose the main specificity of ontology: the knowledge semantics modelling. So, it is useful to address all these shortcomings. This paper presents an approach that allows generating consistent OWL 2 DL ontology versions in a priori way. It also proposes an efficient storage strategy that preserves the semantics aspect of ontology and performs well typical queries with a low storage space. A protégé plug‐in is developed to show the feasibility of the main ideas presented in this paper.